2019
DOI: 10.1038/s41390-019-0463-z
|View full text |Cite
|
Sign up to set email alerts
|

Fetal exposure to mercury and lead from intrauterine blood transfusions

Abstract: BACKGROUND: Mercury (Hg) and lead (Pb) exposure during childhood is associated with irreversible neurodevelopmental effects. Fetal exposure to Hg and Pb from intrauterine blood transfusion (IUBT) has not been reported. METHODS: Fetal exposure was estimated based on transfusion volume and metal concentration in donor packed red blood cell (PRBCs). As biomarkers to quantify prenatal exposure are unknown, Hg and Pb in donor PRBCs were compared to estimated intravenous (IV) RfDs based on gastrointestinal absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Changes in the PLAP conformation can not only alter its function but also cause the structure and function of the placental cell membrane change, which must have adverse effects on the normal fetal development. In addition, PCP is a lipid-soluble substance that can enter the fetus through the placenta and have a direct toxic effect on the fetus [ 30 ]. In Heidelberg Hospital, Germany, during a physical examination of 65 women with a long history of PCP exposure, it was found that its serum PCP content was asked above 20 bucket g/L; thus, the exposure history of PCP in pregnant women will also have adverse effects on the fetus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the PLAP conformation can not only alter its function but also cause the structure and function of the placental cell membrane change, which must have adverse effects on the normal fetal development. In addition, PCP is a lipid-soluble substance that can enter the fetus through the placenta and have a direct toxic effect on the fetus [ 30 ]. In Heidelberg Hospital, Germany, during a physical examination of 65 women with a long history of PCP exposure, it was found that its serum PCP content was asked above 20 bucket g/L; thus, the exposure history of PCP in pregnant women will also have adverse effects on the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in humans, with the deterioration of environmental quality, many environmental pollutants can pass through the way such as respiratory tract, the digestive tract, the skin into pregnant woman's body, and then through the limited tire barrier into fetal body because the fetus is sensitive to the chemical poison effect than adults; in the process of growth and development, if some poisonous substances contact within the womb, it may produce some effects, and adult contact with the substance is not the same as severe damage or even cancer [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was evident that more than 25 μg/dl in newborn blood can cause developmental disorders (Wani et al, 2015); however, growing evidence demonstrates that a blood Pb level less than 25 μg/dl might also increase that risk (Bellinger & Needleman, 2003; Wani et al, 2015). Due to the less active gastrointestinal excretory system, the neonatal Pb level remains slightly higher than that of the mother (Falck et al, 2019), as shown by blood Pb levels of 51 and 49 μg/dl in neonate and mother's blood, respectively (Shannon, 2003). Hence, the relatively higher level of Pb in fetal circulation elevates the risk of abnormalities by various mechanisms.…”
Section: Transportation Of Pb From Maternal Circulation To the Fetal ...mentioning
confidence: 99%
“…The movement of Pb from the mother's body to the fetal circulation follows both passive diffusion and active transport via divalent metal transporters (Falck et al, 2019). According to some published papers, Pb can be transferred by simple diffusion without any involvement of transporters (Goyer, 1990;Shannon, 2003).…”
Section: Mechanisms Of Placental Membrane Crossing By Pbmentioning
confidence: 99%
See 1 more Smart Citation